Financial health and obesity. (May 2021) - Guariglia, Alessandra; Monahan, Mark; Pickering, Karen; Roberts, Tracy
Abstract: We use individual-level panel data from the English Longitudinal Survey of Ageing over the period 2004–2013 to investigate the links between financial health and obesity. We find that having no debt (high savings) is associated with a 3.6 (1.6) percentage point lower probability of having a Body Mass Index in excess of 30. Our results are robust to using different estimation methods, to measuring financial health with a subjective indicator, and adiposity with waist circumference. A lower rate of time preference and lower stress levels may be mechanisms which help to explain the association between good financial health and obesity. Highlights: We investigate the links between financial health and obesity. We focus on the middle aged and elderly in England. No debt is related with a 3.6 percentage point (pp) lower chance of being obese. High savings are associated with a 1.6 pp lower probability of being obese. Mechanisms may be a lower rate of time preferences and lower stress levels.